The invention of the "weird" Southern child: Mapping coloniality in the political problematization of disadvantaged children's lives in the global South. (August 2022) - Araneda-Urrutia, Carlos
In this article, the pervasiveness of coloniality in Southern childhoods' policyscapes is mapped. By analyzing Chilean child nutrition policies, this article illustrates how coloniality fabricates children's ontological "weirdness" to naturalize racial optimization through compulsory abledment. The "weird" Southern child is theorized as the preferred policy subject of an ableist assemblage that racializes disadvantaged children as biologically unfit for civilized life. Finally, this article argues that Childhood Studies must be decolonized by decentering models of childhood where coloniality remains deeply entrenched.